A review on the delivery of plant-based antidiabetic agents using nanocarriers: current status and their role in combatting hyperglycaemia - Zolkepli, Husna; Widodo, Riyanto Teguh; Syed Mahmood; Salim, Norazlinaliza; Awang, Khalijah; Ahmad, Noraini; Othman, Rozana (MDPI, 2022)
Diabetes mellitus is a prevalent metabolic syndrome that is associated with high blood glucose levels. The number of diabetic patients is increasing every year and the total number of cases is expected to reach more than 600 million worldwide by 2045. Modern antidiabetic drugs alleviate hyperglycaemia and complications that are caused by high blood glucose levels. However, due to the side effects of these drugs, plant extracts and bioactive compounds with antidiabetic properties have been gaining attention as alternative treatments for diabetes. Natural products are biocompatible, cheaper and expected to cause fewer side effects than the current antidiabetic drugs. In this review, various nanocarrier systems are discussed, such as liposomes, niosomes, polymeric nanoparticles, nanoemulsions, solid lipid nanoparticles and metallic nanoparticles. These systems have been applied to overcome the limitations of the current drugs and simultaneously improve the efficacy of plant-based antidiabetic drugs. The main challenges in the formulation of plant-based nanocarriers are the loading capacity of the plant extracts and the stability of the carriers. A brief review of lipid nanocarriers and the amphipathic properties of phospholipids and liposomes that encapsulate hydrophilic, hydrophobic and amphiphilic drugs is also described. A special emphasis is placed on metallic nanoparticles, with their advantages and associated complications being reported to highlight their effectiveness for treating hyperglycaemia. The present review could be an interesting paper for researchers who are working in the field of using plant extract-loaded nanoparticles as antidiabetic therapies.